Pengaruh Simpanan Masyarakat dan Tingkat Suku Bunga Kredit Terhadap Penyaluran Kredit Lembaga Perkreditan Desa (LPD) Desa Adat Cemenggaon Periode Tahun 2014-2018 - Ni Putu Dhita Werdi Rahayu; I Ketut Darma; I Nyoman Senimantara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
The existence of LPD in the regions can have a very large socio-economic impact on the weak in rural communities according to their function as a financial institution that collects funds from the community and flows them back into credit. The purpose of this study was to see the effect of public savings and credit interest rates on credit distribution in the LPD at Cemenggaon village. This study used data from 2014-2018 and analyzed using multiple linear regression analysis techniques. The results showed that partially Public Savings had a negative and insignificant effect on Lending, Credit Interest Rates had a negative and significant effect on Lending. Meanwhile, simultaneously the Public Savings, the Interest Rate has a significant effect on Credit Distribution in the LPD at the Cemenggaon village in 2014-2018.